A Comprehensive Study on e-WOM Determinants Influencing Consumers’ Purchase Decision - Dr. Surbhi Jain; Priyanka Rani (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this digital age consumers share their experience about product and service with others digitally. This online sharing is known as electronic words of mouth, online word of mouth, Internet word of mouth (iWOM), Virtual words of mouth (vWOM). It may be between the consumers or may be between thee marketer and consumer in the form of blogs, discussion forum and consumer review. Consumers trust on electronic word of mouth more as it is unpaid form of advertising. After COVID 19 pandemic consumers trust on other consumer reviews increased. They read other customers reviews about product and service before making any purchase decision. There are several e-WOM factors which influence the consumers’ purchase decision. This study focus on those factors which influence consumers’ purchase decision. This research work is based on previous literature of electronic word of mouth. The review showed us e-WOM Quality(Valence), e-WOM Quantity(Volume), Source homophily, Source credibility, Website credibility, Tie strength are the factors which affect customers purchase decision.